Does a close relationship with an adult reduce the risk of juvenile offending for youth with a history of maltreatment? - Baetz, Carly Lyn (Child maltreatment, 2020)
Social support is frequently cited as a protective factor against juvenile offending. The current study examined whether a close relationship with an adult in childhood decreases the risk for offending among individuals with a history of child maltreatment. This research utilized data from a prospective cohort design study in which children with court-substantiated cases of abuse and neglect and nonmaltreated children matched on age, sex, race, and approximate family social class were followed into adulthood (N = 1,196). Having a close relationship with an adult did not decrease risk for delinquent behavior or arrest, but a close relationship with a parent was associated with lower risk for delinquent behavior. Surprisingly, adults with no history of maltreatment who reported having a close relationship with a peer or sibling were more likely to report engaging in violent behavior in adolescence. In total, these findings point to the complexity of development and suggest that although a close relationship with an adult can be protective, the mere presence of such a relationship, without inquiry into the type of relationship, is not sufficient.